Stainless steel corrosion in instrumentation pipe - Nascimento, Jean Victal do; Carvalho, Rafael Adão de; Garcia, Davi Pereira; Maziero, Rômulo; Gomes, Edelize Angelica; Rubio, Juan Carlos Campos (Cadernos UniFOA, 2019)
Corrosion, being a destructive process, causes damage in almost all industrial sectors. In this way, it is harmful both from an economic, social and, especially, safety point of view, as it can cause failures in critical equipment and components of an industrial process. At this point, stainless steels are considered the most corrosion resistant metals. The resistance depends on the chemical composition and microstructure, factors that directly influence the passivation of these materials. The resistance is proportionally related to the addition of chromium (Cr) to the mixture, as well as other alloying elements, among which is the molybdenum (Mo), whose main function is to maximize corrosion resistance in the marine atmosphere, as in case of austenitic stainless steel AISI 316 which presents in the chemical composition a percentage of the element Mo. Austenitic stainless steels are applied in instrumentation systems in tubing for reliability in severe atmospheres in accordance with ASTM A269 which establishes the materials applicable to this function. Thus, the present work presents, through a review and case study, Pitting Corrosion of tubings of austenitic stainless steel AISI 316 in the presence of chloride ions (Cl-) coming from the marine atmosphere. The results show that there is no change in the longitudinal and transverse structure for all analyzed tubes, showing a homogeneous austenitic structure, free of intergranular precipitations.